SPSS as a supprost tool for managerial decisionmaking: an application of the statistical process control - Černý, Josef (Univerzita Pardubice, 2010)
Contemporary world can be characterized as a rapidly changing environment and it also brings not only opportunities, but difficulties too. It seems to be harder and harder to make right decisions in this complicated world. Intuitive way of decision making does not apply to be enough and it should be appropriately completed by exact quantitative methods for decision support. Managers could rely on methods and techniques such as marketing research, analyzing and using the data from marketing research, costs, revenues, profits, input, output modeling, simulation, quality control Fig.s, etc. This variety of methods and techniques is usually supported by software usage, with user-friendly graphical design. One of the appropriate software for decision-making support is SPSS. This paper deals with the SPSS usage for the case of statistical process control which can be a very useful tool for sustaining competitive advantage reached by quality delivered to the end customers.
Keywords: decision-making support; SPSS software; process quality; statistical process control